Answer:
The solution of the given equation is x = -4
Explanation:
Explanation:-
Given expression 4 x - (x +2) +6 = 2 (3 x+8)
Step(i):-
4 x - (x +2) +6 = 2 (3 x+8)
4 x - x -2 + 6 = 6 x + 16
step(ii):-
3 x + 4 = 6 x + 16
subtracting '4' on both sides , we get
3 x + 4 - 4 = 6 x + 16 - 4
3 x = 6 x + 12
Step(iii):-
Subtracting '6x' on both sides , we get
3 x - 6 x = 6 x - 6 x + 12
- 3 x = 12
Step(iv):-
Dividing '-3' on both sides , we get
![(-3x)/(-3) = (12)/(-3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/p1u9k8usemegmhq1wtq8rso4wjllmf4dxv.png)
x = - 4
Final answer:-
The solution of the given equation is x = -4
Verification:-
4 x - (x +2) +6 = 2 (3 x+8)
put x = -4
4 ( -4) - ( - 4 +2) +6 = 2 (3(-4)+8)
-16+2+6 = 2 (-12+8)
-8 = -8
Both are equal